2020
DOI: 10.3389/fmicb.2020.01673
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoantibiotics Display Strong Antifungal Activity Against the Emergent Multidrug-Resistant Yeast Candida auris Under Both Planktonic and Biofilm Growing Conditions

Abstract: Candida auris is an emergent multidrug-resistant pathogenic yeast with an unprecedented ability for a fungal organism to easily spread between patients in clinical settings, leading to major outbreaks in healthcare facilities. The formation of biofilms by C. auris contributes to infection and its environmental persistence. Most antifungals and sanitizing procedures are not effective against C. auris, but antimicrobial nanomaterials could represent a viable alternative to combat the infections caused by this em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
7
29
2
Order By: Relevance
“…We observed that the untreated samples from the different C. auris strains display variations on their phenotypes. This diversity of size and shapes has been described in other works [17,47]. In this work, we expand the current knowledge as we associate the observed specific phenotypes to particular clades.…”
Section: Clade IV (South America Clade)supporting
confidence: 73%
See 1 more Smart Citation
“…We observed that the untreated samples from the different C. auris strains display variations on their phenotypes. This diversity of size and shapes has been described in other works [17,47]. In this work, we expand the current knowledge as we associate the observed specific phenotypes to particular clades.…”
Section: Clade IV (South America Clade)supporting
confidence: 73%
“…We noted that the antibiofilm activity of BiNPs was close to the activity reported for other anticandidal agents during the biofilm formation stage. BiNPs displayed lower antibiofilm potency than that of AgNPs against C. auris biofilms [29,47]. However, the fact that BiNPs display antibiofilm activity should be considered for further research.…”
Section: Binps Inhibit Biofilm Formation By C Aurismentioning
confidence: 97%
“…In addition, we observed that yeast cells continue to attach to each other forming small groups of cells. This observation has been also reported [54]. In their study, they observed that biofilms treated with nanoparticles showed small multibranched groups of cells, usually formed by less than 10 cells.…”
Section: Alterations Produced In C Albicans Cells On Biofilms Due To Arco 2 G 2 (Snme 3 I) 4 (2) Activitysupporting
confidence: 77%
“…In our previous studies, this effect was observed by SEM, including the formation of pores in the membrane of C. albicans [9]. These concurrent damages cause Candida cells to have decreased viability and reduce their ability to withstand the effects produced by treatments [54]. In contrast, the mode of action of antifungals is by targeting specific molecules or cell structures.…”
Section: Effective Prevention Of C Albicans Biofilm Formationmentioning
confidence: 97%
“…Therefore, certain non-antifungal agents alone or in combination with traditional antifungals have been investigated as a potential approach to overcome C. auris -related catheter-associated infections. These include ebselen [ 24 ], miltefosine [ 25 ], farnesol [ 26 ], and silver or bismuth nanoantibiotics [ 27 , 28 ]. To date, three conventional potential line lock solutions have been tested against C. auris biofilms.…”
Section: Discussionmentioning
confidence: 99%